1993
DOI: 10.1021/bi00091a006
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of single-stranded RNA and DNA interactions with oligolysines containing tryptophan. Effects of base composition

Abstract: We have examined the thermodynamics of binding of a series of oligolysines (net charge z = +2 to +10) containing one, two, or three tryptophans to several single-stranded (ss) homo-polynucleotides [poly(A), poly(C), poly(I), poly(dU), poly(dT)] and duplex (ds) DNA in order to investigate the effects of peptide charge, tryptophan content, and polynucleotide base and sugar type. Equilibrium association constants, Kobs, were measured as a function of monovalent salt concentration (KCH3CO2) and temperature by moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
123
2
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(145 citation statements)
references
References 38 publications
19
123
2
1
Order By: Relevance
“…Effect of Peptide Sequence and Reaction Conditions on Nonelectrostatic Interactions-It has been previously reported that short peptides of polylysine containing Trp residues bind to polynucleotides primarily by electrostatic interactions (18,19,(25)(26)(27). To investigate whether these differences with our observations were a consequence of particular peptide sequences or different reaction conditions, we compared the binding of KWK to poly(U) under our conditions at pH 7.4 with the same reaction at pH 5.8, which has been previously well studied (19).…”
Section: Preparation and Characterization Of Peptides And Polynucleotmentioning
confidence: 99%
“…Effect of Peptide Sequence and Reaction Conditions on Nonelectrostatic Interactions-It has been previously reported that short peptides of polylysine containing Trp residues bind to polynucleotides primarily by electrostatic interactions (18,19,(25)(26)(27). To investigate whether these differences with our observations were a consequence of particular peptide sequences or different reaction conditions, we compared the binding of KWK to poly(U) under our conditions at pH 7.4 with the same reaction at pH 5.8, which has been previously well studied (19).…”
Section: Preparation and Characterization Of Peptides And Polynucleotmentioning
confidence: 99%
“…Previously, using circular dichroism and fluorescence, Maurizot et al explained that KWK exhibited a binding affinity to DNA with the order of AA>CC owing to the aromaticity of tryptophan. 26 This result was confirmed by Mascotti and Lohman who characterized the association constant of peptides containing lysine and tryptophan and poly A, poly C, and poly T. 27 They reported that the association constants of oligolysine containing tryptophan decreased in the following order: poly T > poly A > poly C. However, in contrast to previous hypothesis, Figure 2d~2f suggests that this sequence selectivity may not originate from the aromaticity of tryptophan. Instead, this selective preference for DNA sequences may come from lysine residues because KKKKKK shows similar sequence specificity like KWKWKK.…”
mentioning
confidence: 53%
“…This trend is consistent with a previous study reported by Mascotti and Lohman. 27,28 In particular, (KW) 5 KK formed a complex with DNA; the ratio of the peak intensity was 2.1 for the complex over free DNA, which was almost double that of (KW) 2 KK (ratio =1.1).…”
mentioning
confidence: 91%
“…6A) and oligoarginine peptides (Z L = 2 -10) with various ssDNA and ssRNA NAs found that eq 20 with ss ψ = 0.71 (Mascotti & Lohman, 1990) accounts for the salt dependence of these systems at low salt concentrations at low ligand charge (Z L = 2 -4). The full dataset is well fitted if the limiting law expression is augmented to take into account hydration changes upon binding (Mascotti & Lohman, 1990;Mascotti & Lohman, 1993). The linearity of logK obs vs log[salt] has been reported for ligands binding to other polyelectrolytes with varying axial charge densities, ξ, including the polyanionic polysacharride heparin (Mascotti & Lohman, 1995) and polyA•(polyU) 2 triple stranded RNA (Record et al, 1976).…”
Section: )mentioning
confidence: 87%